Penciptaan Sistem Penilaian Kinerja yang Efektif dengan Assessment Centre - Dyah Ayu Lestari Windi Astuti (Jurnal Manajemen Maranatha, 2006)
Competent human resources is one of the most important factors to make an organization to be creative and innovative. To reach thus objective an organization have to up grade the quality of human resource. This upgrading will increase the whole performance of the organization. Organization should manage the best method to develop and motivate their employee, communicating performance appraisal in the organization, making appraisal procedure standard, and using the result for human resource development. This article will reveal everything about performance appraisal with assesment centre method, by the use of this method, the accuracy for individual performance appraisal or in a group should be increasing.